Güncel Anesteziyoloji ve Ağrı Çalışmaları IX (Bahar) - Öncü, Kıvanç; Saylan, Sedat; Akdoğan, Ali; Ertürk, Engin; Şıktaş, Özge; Laflı Tunay, Demet; Tümer, Murat; Şengel, Necmiye; İnan, Gözde and Arslan, Mustafa (Academician Publishing Book DOI Portal, 2024)
-